2006
DOI: 10.2337/diabetes.55.03.06.db05-1015
|View full text |Cite
|
Sign up to set email alerts
|

Necdin and E2F4 Are Modulated by Rosiglitazone Therapy in Diabetic Human Adipose and Muscle Tissue

Abstract: To identify novel pathways mediating molecular mechanisms of thiazolidinediones (TZDs) in humans, we assessed gene expression in adipose and muscle tissue from six subjects with type 2 diabetes before and after 8 weeks of treatment with rosiglitazone. mRNA was analyzed using Total Gene Expression Analysis (TOGA), an automated restriction-based cDNA display method with quantitative analysis of PCR products. The expression of cell cycle regulatory transcription factors E2F4 and the MAGE protein necdin were simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 58 publications
0
21
0
Order By: Relevance
“…We observed that both pref-1 (dlk1) and necdin are down-regulated in both brown and white primary cells. Given the lack of consistency between the different models, we can conclude that there may be substantial differences between the early differentiation transcriptional program characterized in artificially immortalized cell lines (11,45) and the primary brown preadipocyte differentiation program investigated in the present work. In addition, our data contrast with general pRB-E2F brown adipocyte differentiation model (47) developed by using mouse embryo fibroblasts.…”
Section: ) (B)mentioning
confidence: 76%
See 3 more Smart Citations
“…We observed that both pref-1 (dlk1) and necdin are down-regulated in both brown and white primary cells. Given the lack of consistency between the different models, we can conclude that there may be substantial differences between the early differentiation transcriptional program characterized in artificially immortalized cell lines (11,45) and the primary brown preadipocyte differentiation program investigated in the present work. In addition, our data contrast with general pRB-E2F brown adipocyte differentiation model (47) developed by using mouse embryo fibroblasts.…”
Section: ) (B)mentioning
confidence: 76%
“…Pref-1 and necdin have been described as being potential regulators of brown preadipocyte differentiation (11). Necdin has been shown to promote differentiation of skeletal muscle (44) and to be modulated during adipocyte differentiation (45,46). Specifically, necdin down-regulation appears to promote adipogenesis in immortalized brown preadipocytes (11), whereas overexpression in 3T3-L1 white preadipocytes prevents differentiation (45).…”
Section: ) (B)mentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, Wnt signaling in pre-adipocytes maintains an undifferentiated state, while blocking Wnt signaling in myoblasts induces transdifferentiation into adipocytes (Ross et al, 2000). In addition to its role in promoting differentiation of neurons and muscle, necdin has been implicated in adipogenic differentiation (Cypess et al, 2011;Goldfine et al, 2006;Tseng et al, 2005). Ndn, the gene encoding necdin, was the most highly up-regulated gene in immortalized brown pre-adipocytes with decreased differentiation potential due to defective insulin receptor substrate (Irs)-1 signaling (Tseng et al, 2005).…”
Section: Introductionmentioning
confidence: 98%